2016
DOI: 10.1089/ten.tea.2016.0164
|View full text |Cite
|
Sign up to set email alerts
|

Human Corneal Fibroblast Pattern Evolution and Matrix Synthesis on Mechanically Biased Substrates

Abstract: In a fibroblast colony model of corneal stromal development, we asked how physiological tension influences the patterning dynamics of fibroblasts and the orientation of deposited extracellular matrix (ECM). Using long-term live-cell microscopy, enabled by an optically accessible mechanobioreactor, a primary human corneal fibroblast colony was cultured on three types of substrates: a mechanically biased, loaded, dense, disorganized collagen substrate (LDDCS), a glass coverslip, and an unloaded, dense, disorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Since IOP only influences eye patterning and not cell differentiation as noted by Coulombre [43], the factors controlling stromal organization are likely due to keratocyte differentiation. This notion is supported by seminal studies by Ruberti and colleagues who demonstrated that human keratocytes can produce an orthogonal, three-dimensional matrix that resembles the corneal stromal architecture [6769]. This further advocates that the directionality of the mechanical stimuli, which are likely very weak in an expanding cornea, cannot override the patterning behaviour of the corneal stromal cells.…”
Section: Discussionmentioning
confidence: 87%
“…Since IOP only influences eye patterning and not cell differentiation as noted by Coulombre [43], the factors controlling stromal organization are likely due to keratocyte differentiation. This notion is supported by seminal studies by Ruberti and colleagues who demonstrated that human keratocytes can produce an orthogonal, three-dimensional matrix that resembles the corneal stromal architecture [6769]. This further advocates that the directionality of the mechanical stimuli, which are likely very weak in an expanding cornea, cannot override the patterning behaviour of the corneal stromal cells.…”
Section: Discussionmentioning
confidence: 87%
“…The effect of mechanical strain on tenocytes, ligament fibroblasts, and myocytes has been extensively studied . For corneal cells, only some work has so far been done to investigate the mechanical effects with flat, uniaxial load, which cannot totally reflect the in vivo mechanical environment . In the present study, we created a novel static equibiaxial dome‐shaped strain which highly replicated the cornea shape and strain.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, it is not yet known how the topography of the wound may impact the underlying cellular and biological activity and final healing outcome. Although biophysical and topographical cues have been increasingly recognized as key players modulating the biochemical signaling patterns associated with cell differentiation, secretion, and organization of ECM may also be involved 94 96 .…”
Section: Discussionmentioning
confidence: 99%